Mengukur Kualitas Layanan Perpustakaan Universitas Muslim Nusantara Al-Washliyah Medan Menggunakan Metode Libqual - Sari, Julviana Puspita; Sayekti, Retno; Jamil, Khairul (ARZUSIN, 2024)
This research discusses measuring the quality of library services at the Muslim Nusantara Al Washliyah University of Medan using the Libqual method. The aim of the research is to determine the service quality of the Muslim Nusantara Al Washliyah Medan University Library based on three libqual dimensions, namely Affect of Service, Information Control and Library as Place. This type of research is quantitative research with a descriptive approach. The data collection technique in this research was carried out through distributing questionnaires. The sample in this study was 3,159 users of the Nusantara Al Washliyah Medan Muslim University Library from 2021, who were limited using the Slovin formula, so the number of respondents was 97 people. The sampling technique in this research used non-random accidental sampling. The results of this research show that service quality is based on the Affect of Service aspect, users are quite satisfied with the quality of library services or have met the minimum expectations of users with a positive adequancy gap (AG) at a score of 0.03 and the quality of library services is considered good but has not met ideal expectations. what the user wants or is in the tolerance zone with the superiority gap (SG) being negative at a score of -1.01. Based on the Information Control aspect, users are quite satisfied with the quality of library services or have met the minimum expectations of users with a positive adequancy gap (AG) at a score of 0.05 and the quality of library services is considered good but has not met the ideal expectations desired by users or is in the tolerance zone with the superiority gap (SG) being negative at a score of -1.07. Based on the Library as Place aspect, users are quite satisfied with the quality of library services or have met the minimum expectations of users with a positive adequancy gap (AG) at a score of 0.16 and the quality of library services is considered good but has not met the ideal expectations desired by users or is in the zone tolerance with superiority gap (SG) is negative at a score of -1.11.